Les effets géographiques des éruptions volcaniques - Franck Lavigne; Edouard De Belizal (EchoGéo)
The purpose of this paper aims to study the volcanic areas as geographical objects. Geographical analyses help to understand at different scales the levels of impacts induced by volcanic eruptions. Impacts of such events trigger spatial changes across the volcano itself, and can have consequences at regional or even global level in case of outbreaks of greater magnitude. The various examples discussed here focus on hazards, vulnerability and resilience of people living in those volcanic-hazard prone areas.